2018
DOI: 10.3168/jds.2017-14064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrition on the fertility of lactating dairy cattle

Abstract: This meta-analysis of 39 experiments containing 118 treatments explored the effects of diet interventions in early lactation on the proportion of dairy cows pregnant to artificial insemination (AI; pregnancy to AI) and on calving to pregnancy interval. It also identified factors that may explain variation in these responses. The objectives were to identify effects of diet on reproduction, rather than differences between specific dietary interventions. The examination of calving to pregnancy interval used the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 102 publications
2
26
1
2
Order By: Relevance
“…The effects of dietary interventions during transition are complex and multifactorial [40]. Several studies have investigated the effect of nutritional interventions during transition on pregnancy proportions, resumption of cyclicity, calving interval, and number of AI per pregnancy, as measures of reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of dietary interventions during transition are complex and multifactorial [40]. Several studies have investigated the effect of nutritional interventions during transition on pregnancy proportions, resumption of cyclicity, calving interval, and number of AI per pregnancy, as measures of reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it has been recognized that some nutrients improve reproductive performance. Rodney et al in 2018 [40] suggested that increased FA, starch, and metabolizable energy balance intake was positively associated with the proportion of pregnant cows. On the other hand, the authors concluded that the increased intake of rapidly fermentable sugars and high milk protein yield are associated with reduced proportion of pregnant cows.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of dietary interventions during transition are complex and multifactorial [32]. Several studies have investigated the effect of nutritional interventions during transition on pregnancy proportions, resumption of cyclicity, calving interval, and number of AI per pregnancy, as measures of reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it has been recognized that some nutrients improve reproductive performance. Rodney et al in 2018 [32] suggested that increased FA, starch, and metabolizable energy balance intake was positively associated with the proportion of pregnant cows. On the other hand, the authors concluded that the increased intake of rapidly fermentable sugars and high milk protein yield are associated with reduced proportion of pregnant cows.…”
Section: Discussionmentioning
confidence: 99%
“…Further, within-farm variations substantially affected the estimation of the farm's median CFI in this study. e individual CFI can be extended by several factors such as nutrition [34,35], endometritis [36], and poor oestrus detection. Elkjaer et al reported that even mild uterine infection could have an adverse effect on CFI [37].…”
mentioning
confidence: 99%